Sistem Pakar Berbasis Web untuk Diagnosis Penanganan Pasca Panen Kelapa Sawit Menggunakan Metode Naive Bayes - Heny Pratiwi; Muhammad Ibnu Sa'ad; Muhammad Alamsyah Zakaria (Universitas Methodist Indonesia, 2024)
This study aims to design a web-based Expert System that is able to diagnose post-harvest handling of oil palm using the Naive Bayes method. In addition, this study also aims to explore optimal harvesting and post-harvest handling management in order to produce high-quality oil yields. This study was conducted at PT Sawit Sukses Sejahtera, the location where the experts work. Data collection was carried out through interviews with experts related to post-harvest handling of oil palm fruit, as well as literature studies to obtain data relevant to the research topic. The Naive Bayes method is used based on the probability found in the post-harvest handling process of oil palm, while system development follows the ESDLC (Expert System Development Life Cycle) methodology, which is the basis for designing and developing expert systems.